Menejemen Pendapatan Dan Saluran Pemasaran Usaha Tani Bayam di Desa Gundik, Kecamatan Slahung Kabupaten Ponorogo - Ulfi Ita Mu’ami’in; Ahmad Kirom (Social Science Academic, 2023)
Vegetables are food commodities that play an important role, especially as a source of vitamins and minerals. Vegetables have a very large diversity of both types of plants and products consumed. The potential of agricultural land resources that spread from the lowlands to the highlands and the many types of vegetables that exist in Indonesia and one of them is spinach. The aim of the research was to find out the process of planting spinach properly, the harvesting process and the marketing process. The results of this study were to pick spinach every day, after the picking process it was then tied with a rope and washed.